2008
DOI: 10.1007/s10658-008-9368-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recent outbreaks of Dickeya sp. (syn. Erwinia chrysanthemi) slow wilt in potato crops in Israel

Abstract: Suspected Dickeya sp. strains were obtained from potato plants and tubers collected from commercial plots. The disease was observed on crops of various cultivars grown from seed tubers imported from the Netherlands during the spring seasons of 2004-2006, with disease incidence of 2-30% (10% in average). In addition to typical wilting symptoms on the foliage, in cases of severe infection, progeny tubers were rotten in the soil. Six strains were characterised by biochemical, serological and PCR-amplification. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 18 publications
6
85
1
Order By: Relevance
“…The species Dso presented an extremely broad temperature range with a high optimal temperature of +35 o C. These temperatures place Dso in its own group. This is contradictory to the results of Tsror et al (2009), which indicated that Dickeya spp. isolated from potatoes in Israel were not able to grow at temperatures above 41 o C in vitro.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The species Dso presented an extremely broad temperature range with a high optimal temperature of +35 o C. These temperatures place Dso in its own group. This is contradictory to the results of Tsror et al (2009), which indicated that Dickeya spp. isolated from potatoes in Israel were not able to grow at temperatures above 41 o C in vitro.…”
Section: Discussioncontrasting
confidence: 94%
“…to tropical environments and warm temperatures (Tsror et al 2009), was confirmed in this study. Significant differences were noted between Dickeya spp.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…outbreaks have increased substantially since 2001, when the isolates of the new Dickeya species (D. solani) have been found in potato for the first time (Slawiak et al 2009ab). This pathogen has never before been observed in the European climate zone or elsewhere (van der Wolf et al 2014;Tsror et al 2009;Slawiak et al 2009;Laurila et al 2008). Since 2005, the presence of D. solani has been reported in potato in many European countries including The Netherlands, Finland, Poland, Germany, Belgium, France, United Kingdom and Sweden, as well as outside Europe, in Israel and Georgia.…”
Section: Introductionmentioning
confidence: 96%